The Relationship between Maternal Characteristics and Family Health Tasks with the Incident of Stunting in Toddlers in Depok City - Ritanti; Aprilia, Farah (KHD-Production, 2024)
Stunting is an urgent global issue and needs immediate handling in Indonesia. Families have a significant influence in changing behavior to prevent stunting. The aim of this research is to identify the relationship between maternal characteristics and family health duties with the incidence of stunting among toddlers in Depok City. This research uses an analytical observational method with a cross-sectional study. By using 211 mothers with toddlers as the research sample. Based on the results of the Chi Square test, there is a significant relationship between maternal age and the incidence of stunting in toddlers (p=0.038). However, there was no significant relationship between the number of children and the incidence of stunting (p=0.899). In addition, the results of the analysis showed a significant relationship between the mother's last education (p=0.027) and the mother's employment status (p=0.033) with the incidence of stunting in toddlers. This research also found that all stages of family health tasks were significantly related to the incidence of stunting in toddlers (p<0.05), and there was a significant relationship between the total value of the ability to carry out family health tasks and the incidence of stunting (p=0.011). These findings emphasize the need for comprehensive family-based health services to overcome the problem of stunting in toddlers.